2003
DOI: 10.1007/s00340-003-1196-5
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and wavelength dependences of electro-optic coefficients in inorganic crystals

Abstract: The frequency dependence of electro-optic coefficients in congruent and stoichiometric LiNbO 3 ,L i T a O 3 , β-BaB 2 O 4 and KTiOPO 4 was determined and compared to each other for the first time in a wide frequency range from DC up to 150 MHz. The measurements have been investigated as a function of laser wavelength from 0.5 to 1.3 µm. Clamped and unclamped electro-optic coefficients as well as the acoustic contribution have been established for each crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 10 publications
2
31
0
Order By: Relevance
“…We note that the observed photorefractivity reduction cannot be explained by invoking the wavelengthdispersion of the parameter R eff , since the changes of the refractive indices are fractionally small when going from λ 1 to λ 2 , and the measured electro-optical coefficients of lithium niobate have a rather weak dispersion over the same wavelength range [23]. Noting that the two measurements are performed in different ranges of green-beam intensities, the reduction could be due to a decrease of the sensitivity δS when the green-beam intensity is increased.…”
Section: Discussionmentioning
confidence: 89%
“…We note that the observed photorefractivity reduction cannot be explained by invoking the wavelengthdispersion of the parameter R eff , since the changes of the refractive indices are fractionally small when going from λ 1 to λ 2 , and the measured electro-optical coefficients of lithium niobate have a rather weak dispersion over the same wavelength range [23]. Noting that the two measurements are performed in different ranges of green-beam intensities, the reduction could be due to a decrease of the sensitivity δS when the green-beam intensity is increased.…”
Section: Discussionmentioning
confidence: 89%
“…BBO Q-switches have been reported to exhibit negligible piezoelectric ringing at repetition rates of up to 6 kHz. Only a small acoustic contribution around 5 % to the total electro-optic coefficient has been measured [98] explaining why no piezoelectric ringing is detected with BBO Pockels cells up to 6 kHz [99]. The combination of high optical damage threshold, (single-shot bulk damage threshold value, up to 50 GW/cm 2 at 1064 nm [100]) reduced piezoelectric ringing and relatively low insertion loss makes this crystal particularly attractive for electro-optic Q-switching of high peak and average power solid-state lasers [96].…”
Section: The Pockels Cellmentioning
confidence: 99%
“…Recently Abarkan et al [7] experimentally showed that the coefficients r T and r S for a number of crystals can differ substantially. This is especially true for lithium niobate (LNB) and lithium tantalate (LTA).…”
Section: The Pockels Effectmentioning
confidence: 99%
“…This difference is determined by the acoustic contribution in the intermediate frequency range in which the optical signal oscillates with a period that is governed by the main piezoelectric-resonance frequencies. The accompanying "piezoelectric ringing" limits the use of many crystals as Q-switches at high repetition rates, because the amplitude r a = r Tr S is directly related to the strength of the acoustic resonance [7]. Moreover, rather small coefficients r S can lead to undesirably high driving voltages when the cavity in Pockels cells is rapidly turned on and off.…”
Section: The Pockels Effectmentioning
confidence: 99%
See 1 more Smart Citation